On the Functionality of Coatings for Cathode Active Materials in Thiophosphate‐Based All‐Solid‐State Batteries. Issue 24 (8th May 2019) - Culver, Sean P.; Koerver, Raimund; Zeier, Wolfgang G.; Janek, Jürgen
Abstract: The last decade has seen considerable advancements in the development of solid electrolytes for solid‐state battery applications, with particular attention being paid to sulfide superionic conductors. Importantly, the intrinsic electrochemical instability of these high‐performance separators highlights the notion that further progress in the field of solid‐state batteries is contingent on the optimization of component material interfaces in order to secure high energy and power densities, while maintaining device safety and a practical cycle life. On the cathode side, the need for a protective coating to inhibit solid electrolyte degradation is clear; however, a mechanistic understanding of the coating functionality remains unresolved, and there is still much room for improvement regarding the methodology and associated material properties. Herein, the essential requirements for a suitable coating are specified and fundamental considerations are discussed in detail. Additionally, this article will provide an overview of the various material classes, assessment protocols and practical coating methods, as well as an outlook on the development of coatings for cathode active materials in thiophosphate‐based solid‐state batteries. Abstract : The desired transition from conventional lithium‐ion battery technologies to all‐solid‐state battery architectures will require a rational tailoring of the diverse, performance‐limiting component material interfaces. On the cathode side, the need for protective coatings to prevent solid electrolyte degradation is clear; however, there is still much to be done in order to achieve high‐performance solid‐state batteries with a practical cycle life.